ANALISIS FAKTOR-FAKTOR EKSTERNAL DAN INTERNAL YANG BERPENGARUH TERHADAP KECURANGAN AKUNTANSI (Studi Empiris Pada Rumah Sakit Umum Daerah di Provinsi Riau) - Karunia, Khairinnisa; Emrinaldi, Emrinaldi; Devi Safitri, Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to determine (1) how the influence of internal control to accounting fraud (2) how the influence of law enforcement to accounting fraud (3) how the influence of compliance of accounting rules to accounting fraud (4) how the influence of job satisfaction to accounting fraud. The population in this research is all local public hospital in Riau Province. The sample on this study are 6 local public hospitals in Riau Province. There are 48 respondents that used as a samples. The technique of data gathering is by spreading the questionnaire provided to all finance and accounting staff at the local public hospitals in Riau Province. For analysis the hypothesis of these variable is using SmartPLS program. The results in this study show that internal controls have an influence to accounting fraud, law enforcement have an influence to accounting fraud, and compliance of accounting rules have an influence to accounting fraud. But, job satisfaction does not have an influence to accounting fraud.Keywords : Accounting fraud, Internal Control, Law Enforcement, Compliance of Accounting Rules, Job Satisfaction.